Design and Build a Water Pump Control System Using a Monitoring System Based on Telegram Communication - Muntasiroh, Laily; Solichan, Achmad; Ikhwanuddin, Muhammad (Electrical Engineering Department Faculty of Engineering State University of Gorontalo, 2024)
creatures which is very important in a everyday, therefore ensuring that there is always water available in the reservoir is very important. However, in the process of controlling and monitoring water in the reservoir there are several problems, for example the location of the reservoir is on the top floor of the building and access is too difficult for monitoring the water reservoir. By designing a water pump control system with NodeMCU ESP 8266 using a Telegram communication-based monitoring system, system design using research and development methods can provide solutions and resolve existing problems. Via Smartphone, computer or laptop you can control water pumps and monitor water levels based on Telegram communication anytime and anywhere with Internet of Things (IoT) technology. Using an ultrasonic sensor type HC-SR04 to detect the water level in the reservoir, the process with the NodeMCU ESP 8266 board can be controlled and monitored using the Telegram massager application. The design has been carried out to test the function of every aspect of the components used, such as manual control, automatic systems, results read by ultrasonic sensors, Telegram communications and Telegram notifications that can run and optimally.